Alicja w krainie czarow - Busquets, Carlos; Jarmolkiewicz, Elzbieta (Zielona Gora : E. Jarmolkiewicz, 1994)
An adaptation of Lewis Carroll's Alice in Wonderland, for young children. Ages 4-7.
Keywords: Alice (Fictitious character : Carroll) -- Juvenile literature